Coexistence and interplay of pseudomagnetism and flexoelectricity in few-layer rippled graphene - Jinrong Xu; Zhenyu Zhang; Ping Cui (npj Quantum Materials, 2024)
Abstract The mechanical strain has been widely exploited as an effective knob to induce various intriguing phenomena in two-dimensional materials, notably the emergence of pseudomagnetism and flexoelectricity. Here, using tight-binding model calculations supplemented with selective crosschecks within first-principles theory, we present the first demonstration of coexisting pseudo magnetism and flexoelectricity in both rippled graphene monolayer and bilayer and further reveal the interplay of the strain-induced phenomena. For a rippled monolayer, lattice distortion induces the emergence of a synchronously modulated pseudomagnetic field, which in turn breaks the charge neutrality of the sublattices, as manifested by the concomitant presence of in-plane flexoelectricity. For a rippled bilayer, pseudomagnetism substantially enhances in some regions of the bottom layer and disappears in the corresponding regions of the top layer due to pronounced interlayer coupling, or vice versa, accompanied by simultaneous in-plane and out-of-plane polarizations with opposite directions. Collectively, these findings offer new opportunities for developing graphene-based multiferroic devices.